2011
DOI: 10.1016/j.biopsych.2010.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Incubation of Cue-Induced Cigarette Craving During Abstinence in Human Smokers

Abstract: Background Abstinent drug users remain at risk for relapse long after withdrawal subsides. Animal studies indicate that responses to drug-related cues not only persist, but increase, with abstinence, a phenomenon termed “incubation of drug craving”. It is unknown if cue-induced craving increases, decreases, or remains constant with abstinence in humans. We investigated effects of abstinence on cue-induced craving in cigarette smokers. Methods Eighty-six non-treatment-seeking, adult smokers (≥ 10 cigarettes d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
159
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(178 citation statements)
references
References 23 publications
13
159
2
2
Order By: Relevance
“…Notably, evidence suggests that relapse risk remains high or even grows ('incubates') over periods of abstinence (Grimm et al, 2001;Bossert et al, 2005;Lu et al, 2004;Bedi et al, 2011). Therefore, rather than evaluating drug-seeking behavior immediately after extinction training, we conducted our tests 4 weeks later to allow potential spontaneous recovery of responding and to assess the longevity of any effects on extinction following this 'incubation' period.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, evidence suggests that relapse risk remains high or even grows ('incubates') over periods of abstinence (Grimm et al, 2001;Bossert et al, 2005;Lu et al, 2004;Bedi et al, 2011). Therefore, rather than evaluating drug-seeking behavior immediately after extinction training, we conducted our tests 4 weeks later to allow potential spontaneous recovery of responding and to assess the longevity of any effects on extinction following this 'incubation' period.…”
Section: Introductionmentioning
confidence: 99%
“…Recent animal studies have suggested that the drugseeking response to drug-related cues increases with prolonged drug abstinence [12,13], and human studies have indicated similarly that cue-induced cigarette craving increases across the time-course of abstinence [14]. This suggests a complex and dynamic relationship between cue-induced craving and abstinence, including potentially abstinence-induced craving.…”
Section: Will Peak Provoked Craving Prove Superior To Cue-reactivity?mentioning
confidence: 98%
“…It is therefore perhaps unsurprising that they correlate only minimally with self-report measures of craving [11], despite both ostensibly capturing a common underlying construct. What this illustrates is that ostensibly objective measures of psychological phenomena which have good face validity may lack basic psychometric properties such as acceptable internal reliability.Recent animal studies have suggested that the drugseeking response to drug-related cues increases with prolonged drug abstinence [12,13], and human studies have indicated similarly that cue-induced cigarette craving increases across the time-course of abstinence [14]. This suggests a complex and dynamic relationship between cue-induced craving and abstinence, including potentially abstinence-induced craving.…”
mentioning
confidence: 98%
“…Des témoignages recueillis auprès d'utilisateurs abstinents confirment que la présence de stimuli associés à la consommation o 2 prolonge encore davantage la sensation de craving, ce que l'on appelle la période « d'incubation » (Bedi et al, 2011). Par exemple, des exconsommateurs d'héroïne rapportent avoir ressenti du craving jusqu'à trois mois après l'arrêt de la consommation, 50 % décrivant un niveau d'intensité aussi élevé après un mois que durant la première semaine d'abstinence (Dhawan, Kumar, Yadav et Tripathi, 2002).…”
Section: éPidémiologie Du Craving Et Phénomène D'incubationunclassified